When the label matters: adsorption of labeled and unlabeled proteins on charged surfaces - Romanowska, Julia; Kokh, Daria B.; Wade, Rebecca C. (Nano letters, 2015)
Fluorescent labels are often attached to proteins to monitor binding and adsorption processes. Docking simulations for native hen egg white lysozyme (HEWL) and HEWL labeled with fluorescein isothiocyanate show that these adsorb differently on charged surfaces. Attachment of even a small label can significantly change the interaction properties of a protein. Thus, the results of experiments with fluorescently labeled proteins should be interpreted by modeling the structures and computing the interaction properties of both labeled and unlabeled species.
Gesehen am 02.07.2020